The moderating role of self-efficacy on the relationship between Ego-resilency and self-esteem of students with and without passion - Agnieszka Bochniarz; Urszula Olejnik (Studia z Teorii Wychowania)
The text is the first in a series of studies on popular legal culture. The research is carried out as part of a grant from the Innovation Leaders Academy pilot program. Organizer: Center for Academic Entrepreneurship and Technology Transfer of the Nicolaus Copernicus University in Toruń. The aim of the research, in the theoretical, research and practical spheres, is to develop social implementation. The implementation will include modern tools for legal education for selected target groups (e-book, internet applications). The research is carried out for the purposes of description under the third evaluation criterion: the impact of scientific activity on the functioning of society and the economy. The research is interdisciplinary; it is on the border of several pedagogical subdisciplines: general pedagogy, andragogy and pedeutology. This research is in the mainstream of legal pedagogy, which takes place in the structure of legal sciences.